The heartbeat of Old Testament theology : three creedal expressions - Boda, Mark J. (Grand Rapids,MI Baker Academic, 2017)
In The Heartbeat of Old Testament Theology, a volume from the Acadia Studies in Bible and Theology series, respected scholar Mark Boda reveals the ways in which the redemptive pulse of God expands to all creation through three rhythmical doctrinal expressions--the narrative, character, and relational creeds--that recur throughout the Old Testament and express its core theology. He then traces these redemptive and creational pulses into the New Testament and shows their relevance for today's Christian community.
Taking the pulse of Old Testament theology: past and present -- The narrative rhythm: God's historical action -- The character rhythm: God's active character -- The relational rhythm: God's relational identity -- Integrating the creedal rhythms -- Creation and the creedal rhythms -- Taking the Old Testament pulse in the New Testament -- Taking the Old Testament pulse in the Christian life -- Postscript: Calling for response -- Appendix: Biblical theology and the Old Testament.
Includes bibliographical references and indexes.
Keywords: Bible. -- Theology; Bible -- Theology